2018
DOI: 10.1002/aqc.2860
|View full text |Cite
|
Sign up to set email alerts
|

Linking pipefishes and seahorses to seagrass meadows in the Venice lagoon: Implications for conservation

Abstract: Seagrass meadow degradation and loss is one of the major threats to fish biodiversity in coastal marine and lagoon ecosystems in the Mediterranean. Pipefishes and seahorses (family Syngnathidae) are particularly affected by loss of seagrass meadows and other structured habitats, on which they rely for survival and reproduction. Despite their charismatic appearance and peculiar behaviour, their habitat ecology is still poorly understood in Mediterranean coastal waters. This study focuses on syngnathid assemblag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…ation between the pipefish species shown in the present study were also described by Scapin et al (2018), who highlighted a more generalist behavior in habitat choice of S. abaster, mostly found in association to algal beds and low-density seagrass meadows, compared with S. typhle, which appear to be dense-seagrass specialists. N. ophidion was also expected to be a dense-seagrass specialist (Scapin et al, 2018), but it was mainly found in C. nodosa during our study. Pipefish exhibit a high degree of trophic specialization compared to other epibenthic marine teleosts (Gürkan, 2008).…”
Section: Discussionsupporting
confidence: 86%
“…ation between the pipefish species shown in the present study were also described by Scapin et al (2018), who highlighted a more generalist behavior in habitat choice of S. abaster, mostly found in association to algal beds and low-density seagrass meadows, compared with S. typhle, which appear to be dense-seagrass specialists. N. ophidion was also expected to be a dense-seagrass specialist (Scapin et al, 2018), but it was mainly found in C. nodosa during our study. Pipefish exhibit a high degree of trophic specialization compared to other epibenthic marine teleosts (Gürkan, 2008).…”
Section: Discussionsupporting
confidence: 86%
“…In particular, N. ophidion and S. typhle show a greater response to extent and spatial arrangement of seagrass meadows in the seascape, as well as a positive response to larger mosaic patches. This emphasises their role as seagrass specialists that could be employed as indicators of seagrass habitat status, as already pointed out for the Venice lagoon (Scapin et al 2016;Scapin et al 2018).…”
Section: Discussionmentioning
confidence: 72%
“…Syngnathids exhibit preferences for different canopy heights in seagrass meadows at the site scale in the Venice lagoon (Malavasi et al 2007;Scapin et al 2018). This paper emphasises that species of this family show a different response to canopy height also at the mosaic scale.…”
Section: Discussionmentioning
confidence: 85%
“…Similarly, presence/absence of S. pavo , Hippolytidae and Z. ophiocephalus were predicted with high accuracy; hence, the inclusion of such species in the reference assemblages can be inferred due to their relatively high probability of presence. S. typhle and N. ophidion are highly specialized pipefish that have developed morphological and behavioural adaptations to thrive in dense, highly structured seagrass meadows (Franzoi et al, ; Malavasi et al, ; Scapin, Cavraro, et al, ). The peacock blenny ( S. pavo ), grass goby ( Z. ophiocephalus ) and hippolytid shrimps are other common species of seagrass habitats in Mediterranean coastal lagoons (d'Udekem d'Acoz, ; Franzoi et al, ; Scapin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Nekton in transitional water ecosystems play a key role in mediating ecological processes and supporting ecosystem functions and services (Elliott & Hemingway, ; Kneib, ; McLusky & Elliott, ; Pérez‐Ruzafa, Marcos, & Pérez‐Ruzafa, ). Abundant and diverse nekton assemblages in estuaries and coastal lagoons are supported by seagrass meadows, which feature large proportions of habitat specialists as well as endangered and iconic species that utilize seagrass habitats for shelter, food and reproduction (Browne, Baker, & Connolly, ; Franco et al, ; Franzoi, Franco, & Torricelli, ; Scapin et al, ; Shokri, Gladstone, & Jelbart, ; Vincent, Foster, & Koldewey, ). In addition, juveniles of many commercially important species are known to exploit seagrass beds in estuaries and coastal lagoons as nursery areas (Blandon & Zu Ermgassen, ; Pihl et al, ; Whitfield, ).…”
Section: Introductionmentioning
confidence: 99%